1995
DOI: 10.1136/gut.36.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules in inflammatory bowel disease.

Abstract: The ability of leucocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
120
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 42 publications
(4 reference statements)
8
120
1
Order By: Relevance
“…Recently, circulating forms of several adhesion molecules, including E-cadherin, E-selectin, ICAM-1 and VCAM-1, have been described with their concentrations being increased in inflammatory and malignant diseases, e.g. malignant melanoma, gastrointestinal cancer, lymphoma, hepatocellular cancer (Gearing et al, 1992;Banks et al, 1993;Katayama et al, 1994;Jones et al, 1995;Wittig et al, 1996). Although little investigated so far, soluble forms of adhesion molecules have been linked to clinical behaviour of tumours.…”
mentioning
confidence: 99%
“…Recently, circulating forms of several adhesion molecules, including E-cadherin, E-selectin, ICAM-1 and VCAM-1, have been described with their concentrations being increased in inflammatory and malignant diseases, e.g. malignant melanoma, gastrointestinal cancer, lymphoma, hepatocellular cancer (Gearing et al, 1992;Banks et al, 1993;Katayama et al, 1994;Jones et al, 1995;Wittig et al, 1996). Although little investigated so far, soluble forms of adhesion molecules have been linked to clinical behaviour of tumours.…”
mentioning
confidence: 99%
“…[8] who described how increased expression of MAdCAM-1, but not of VCAM-1 or intercellular adhesion molecule-1(ICAM-1), mediates the lymphocyte-endothelial cell adhesive interaction in a model of chronic colitis induced by transferring CD45RBhigh T-cells to SCID mice. There are indeed several reports indicating that antibodies against other adhesion molecules (ICAM-1 or VCAM-1) attenuate the increased leucocyte adhesion in intestinal venules [7,18,19]. In the case of ICAM-1, however, we have already reported that up-regulated ICAM-1 is not involved in T lymphocyte-endothelial adhesion in the inflamed colon [15].…”
Section: Discussionmentioning
confidence: 73%
“…We have also demonstrated the functional importance of elevated MAdCAM-1 levels in different animal models of colitis after immunoneutralization of MAdCAM-1 [4,5]. Although other adhesion molecules such as vascular cell adhesion molecule-1 (VCAM-1) are up-regulated in the intestinal mucosa during inflammatory bowel diseases [3,6,7], the possible involvement of VCAM-1 in lymphocyte recruitment to the inflamed gut is still controversial [4,8]. The relative functional importance of MAdCAM-1 and VCAM-1 in altered lymphocyte trafficking should thus be elucidated.…”
Section: Introductionmentioning
confidence: 88%
“…Osteopontin and tumor necrosis factor receptor signaling (TNFRS) F14 are genes associated with fibrosis/cell adhesion molecules [1,13]. Blockade of these cell adhesion molecule interactions prevents the trafficking of leukocytes across the vascular endothelium and, subsequently, into the parenchymal tissue [14][15][16]. Alpha-4 integrins bind additional ligands in tissues, including OPN and epitopes of fibronectin.…”
mentioning
confidence: 99%